PEMANFAATAN LIMBAH AIR KELAPA MENJADI PRODUK COCO CIDER : KAJIAN PENAMBAHAN GULA DAN WAKTU FERMENTASI - Luh Putu Wrasiati (Bumi Lestari Journal of Environment, 2013)
AbstractThe coconut waste water contain some nutrients, micronutriens, and minerals such as vitaminC, biotin, riboflavin, folic acid, amino acid, carbohydrate, calcium, phosphorous and iron.The product of coconut waste water is popularly known as nata-de-coco. Besides that, thecoconut waste water can also produced as alcohol beverages like coco cider. This researchwas conducted in order to observe the effect of sucrose addition and fermentation time onthe characteristics of coco cider, and to determine the best characteristics of coco cider.This research is expected to provide the information about the amount of sugar should beadded and fermentation time in production of coco cider. The design experiment used in thisresearch was the randomized complete design with two factors, i.e. the ratio of sugar added(5, 10, 15, and 20%) and the fermentation time (2, 4, and 6 days). The variables observedincluded alcohol content, total sugar content, pH, and sensory evaluation such as taste,aroma, and overall acceptance. The results indicated that the interaction between sucroseaddition and fermentation time significantly affected the alcohol content and total sugarcontent of coco cider, the more the sucrose added and the longer the fermentation time, thehigher the alcohol content and the less the total sugar content. The sensory evaluationindicated that the good coco cider was produced from 10 percen of sucrose and fermentedin two days with the characteristics: the score of taste, aroma and overall acceptance wasbetween 3 and 4, alcohol content was 5.3, pH was 3.9, and total sugar content was 10.75percents.